Green Chemistry-Based Reaction Rate Practice Through Online Media: An Analysis of Teachers' and Students' Responses - Chamidah, Afifah Nur; Mulyanti, Sri (Universitas Islam Negeri Raden Intan Lampung, 2021)
Reaction rate is one of the subjects in chemistry that students must fully understand, both theoretically and skillfully. However, current conditions require learning to be carried out online, including practicum on reaction rates. The research team tried to design an online practicum on the topic of determining the order of a reaction by using methods, tools, and materials that are cheap and easy to obtain, this practicum as an alternative solution in learning chemistry practicum during the pandemic. The practicum was recorded in the form of a video to be uploaded on Youtube, then the video was distributed to get responses from respondents who watched it. Based on the survey results from 30 respondents, the practicum was stated to be very good and applicable, as seen from the average value of the responses that were close to perfect. So it can be concluded that this practicum is highly recommended for teachers to apply to their students.